A personal perspective on prediction of saline water evaporation from porous media. Issue 4 (22nd February 2022) - Shokri-Kuehni, Salome M. S.; Sahimi, Muhammad; Shokri, Nima
Abstract: Using the great opportunity for contributing a paper to the Special Issue of Drying Technology on the occasion of 30 years of pore-network modeling of drying, we discuss some of the open questions regarding description of saline water evaporation from porous media, which is a topic relevant to a number of environmental and engineering processes and applications, including but not limited to soil salinization, preservation of building materials, and CO2 sequestration. This note is not meant to be an in-depth review article, but more to serve as a summary of open challenges regarding prediction of saline water evaporation from porous media, based on the authors' recent experimental and computational results and analysis. We focus on the formation of crystalized porous salt layers during drying of porous media and their consequences on the evaporative water losses. Suggestions are made on the future perspective and research directions to predict saline water evaporation from porous media.